2019
DOI: 10.1145/3318143
|View full text |Cite
|
Sign up to set email alerts
|

Ambiguity as a Resource to Inform Proto-Practices

Abstract: Skin conductance is an interesting measure of arousal level, largely unfamiliar to most end-users. We designed a mobile application mirroring end-users' skin conductance in evocative visualizations, purposefully made ambiguous to invite rich interpretations. Twenty-three participants used the system for a month. Through the lens of a practice-based analysis of weekly interviews and the logged data, several quite different-sometimes even mutually exclusive-interpretations or proto-practices arose: as stress man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 85 publications
(116 reference statements)
2
34
0
Order By: Relevance
“…Second, users may have preconceived ideas that colour their meaning-making processes. In a study lasting for a month Sanches and colleagues [40] observed that different user groups came up with entirely different interpretations of an EDA-enabled (Electrodermal Activity), real-time, monitoring system. Participants involved in sports assumed that they would be able to see recovery patterns through their biodata, while people suffering from stress issues looked for indicators of stress or emotion patterns.…”
Section: Sensemakingmentioning
confidence: 99%
“…Second, users may have preconceived ideas that colour their meaning-making processes. In a study lasting for a month Sanches and colleagues [40] observed that different user groups came up with entirely different interpretations of an EDA-enabled (Electrodermal Activity), real-time, monitoring system. Participants involved in sports assumed that they would be able to see recovery patterns through their biodata, while people suffering from stress issues looked for indicators of stress or emotion patterns.…”
Section: Sensemakingmentioning
confidence: 99%
“…Particularly in tangible and embodied interaction research, there has been a growing exploration of how metaphorical representation of bodily experiences can be effectively implemented into interaction models [7,8,51,55]. For instance, such metaphors have been used for the design of tangible learning systems [10], to foster collaborative shared experiences [23], or to support the self-regulation of attention and affect [9,38].…”
Section: Exploring Embodied Experiences In Hcimentioning
confidence: 99%
“…Applications using ambiguous sensing-based interactions are mostly represented in art-related, performative or playful contexts, to create a landscape of provocative and unconventional experiences inviting reflection [2]. In HCI, ambiguity is seen as a problem, but it is introduced as a resource for design [25]. The range of applications using the contextual ambiguity of the sensor is less crowded but present in examples like the POUTs [20].…”
Section: Ambiguity and Playmentioning
confidence: 99%